2019
DOI: 10.1061/(asce)nh.1527-6996.0000330
|View full text |Cite
|
Sign up to set email alerts
|

Roadblocks to Housing after Disaster: Homeless Veterans’ Experiences after Hurricane Sandy

Abstract: Individuals who are homeless are disproportionately likely to experience negative outcomes during disasters. Setbacks to their efforts to access needed services, such as transitional housing and case management to help them find stable permanent housing, are a common occurrence. This article explores the experiences of nine US military veterans who were homeless during Hurricane Sandy in 2012 and their efforts to find permanent housing in the 3 years following the storm. It focuses on the sources of support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This study also found that Veterans who were enrolled in VA housing or supportive services, particularly GPD transitional housing programs, were dramatically more likely to be vaccinated. These programs provide a vital safety net for Veterans who lack basic resources, particularly during disasters which often disproportionately affects this population and disrupts access to care and services [51,52]. found that Veterans enrolled in GPD programs reported no access barriers to receiving a COVID-19 vaccine, as GPD staff members assisted in scheduling appointments for Veterans, providing transportation to vaccine clinics, or facilitating vaccination onsite.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that Veterans who were enrolled in VA housing or supportive services, particularly GPD transitional housing programs, were dramatically more likely to be vaccinated. These programs provide a vital safety net for Veterans who lack basic resources, particularly during disasters which often disproportionately affects this population and disrupts access to care and services [51,52]. found that Veterans enrolled in GPD programs reported no access barriers to receiving a COVID-19 vaccine, as GPD staff members assisted in scheduling appointments for Veterans, providing transportation to vaccine clinics, or facilitating vaccination onsite.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate success of the Santa Rosa GPD program that relocated to a shelter in getting all eight of its Veterans into permanent housing before their 2 years of program eligibility expired suggests that the benefits of disaster preparedness may not always be visible, but can pay dividends in the long run as program participants can be free of worry about their immediate future and focus on their long-term objectives. The role of such safety net transitional housing programs during disasters in homeless Veterans' postdisaster success in exiting homelessness has been suggested in prior qualitative research (Gin et al, 2019a).…”
Section: Disaster Preparednessmentioning
confidence: 99%
“…After a disaster, local CBOs remain in the community, playing a critical role in recovery for both preexisting homeless and newly homeless individuals. 15 However, these CBOs are typically not connected with crucial emergency management partnerships, resources, and networks, 10 creating challenges in identifying recovery resources, ensuring effective outreach, and delivering culturally competent services. Local emergency planners can enhance this process through establishing relationships with homeless-serving CBOs, identifying opportunities to partner, developing awareness of their capacity and limitations, and establishing agreements for CBOs to participate in addressing community needs during disasters.…”
Section: E63mentioning
confidence: 99%